Modeling Innovation-Driven National Economic Growth Using PLS-SEM - Silalahi, Renta Ristia Elfrida; Diawati, Lucia (ITB Graduate School Conference, 2025)
Innovation is a key pillar of national competitiveness, as outlined in the Global Competitiveness Index (GCI), and is strongly aligned with the Sustainable Development Goals (SDGs), particularly Goal 8 on inclusive economic growth and Goal 9 on industrial innovation. While the GCI emphasizes innovation as a strategic driver, the Global Innovation Index (GII) provides a more detailed framework for assessing national innovation capacity. This paper aims to analyze the lagged effect of innovation on economic performance by linking GII 2022 indicators to 2023 GDP per capita. Exploratory factor analysis was used to identify three latent constructs: knowledge infrastructure, institutional quality, and human capital. These constructs were analyzed through PLS-SEM and regression analysis. The model explains 73.5% of the variance in the logarithm of GDP per capita. Results indicate that innovation capacity, particularly through institutional strength and human capital development, has a significant delayed impact on economic growth. These findings suggest that strengthening national innovation systems may serve as an effective policy instrument for enhancing competitiveness and fostering sustainable, innovation-driven development consistent with the SDGs.